On the Empirics of Foreign Aid and Growth - Carl-Johan Dalgaard; Henrik Hansen; Finn Tarp (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
This paper takes a fresh look at two issues in the aid effectiveness debate. We begin by providing theoretical foundations for the various claims made with regard to the effectiveness of aid in stimulating long-run productivity. When foreign aid is modelled as an exogenous transfer of income or capital in a standard OLG model, aid wil in general impact on productivity. Moreover in this setting, the returns to aid may depend on both policy and structural characteristics. Next we reexamine the case for policy-based conditionality. Our empirical analysis suggests that aid is generally effective, even in bad environments. However, the degree to which aid enhances growth depends on climate-related circumstances. In light of this finding we argue that the Collier-Dollar allocation rule should be seriously reconsidered by donor agencies.
Keywords: 330; Entwicklungshilfe; Wirtschaftswachstum; Wirkungsanalyse; Neue Wachstumstheorie; Theorie